PEMBENTUKAN PORTOFOLIO OPTIMAL SAHAM INDEKS LQ-45 DAN JAKARTA ISLAMIC INDEX (JII) - Rahadjeng, Erna Retna (Fakultas Ekonomi, UIN Maliki Malang, 2014)
This research is a case study conducted in EfekIndonesia Exchange under the title â€Determinationof Optimal Portfolio shares and shares of LQ45 JIIâ€. The purpose of this study is to identify the combinationof shares and the amount of the proportion of funds that can form the optimal portfolio and to determine thelevel of risk and return of the optimal portfolio is formed. Sampling method in this study, namely purposivesampling. The criteria in this study is that stocks are always included in the index and the index JII LQ45 overthe study period. The method used in determining the optimal portfolio is the single index model. The conclusionof this research is that there are three stocks, and four 45 LQ JII stocks that can form the optimal portfolio,which shares BNII, AALI, and UNSP for LQ 45, while for the stock is AALI JII, KLBF, TLKM, and INCO. Riskportfolio of 45 stocks LQ 1.635116% with a repayment rate of 0.639931%, while the risk portfolio of stocks JII-0.0194424% with portfolio returns of 0.191527%. Thus, the purpose and formulation of the problem unanswered.